La gestión escolar como mecanismo de mejora de la calidad educativa en la escuela mariscal Antonio José de sucre del cantón Saquisili año lectivo 2015 propuesta de un modelo de gestión escolar y vinculación comunitaria para mejorar la calidad educativa. - Unaucho Quishpe, Blanca Elena (2016)
In today's society, where processes are at the service of the globalized economy, it is important to rethink school actions to the light of management quality in the service provided. Quality management school involves all member of the educational work, in order to provide a comprehensive quality service to the society. Management is a key element of the quality of schools performance, especially when the decentralization process increase in the educational systems. Effective schools and the success of its processes are based on good management that affects the organizational climate, in the forms of leadership and institutional driving, optimum utilization of human resources and time in planning tasks and distribution of work and productivity, the efficiency of the administration and performance of material resources, and in the quality of each of the processes which are built into the same. Primary education as a phase of new forms of learning, it is by the accelerated society’s transformation, today students that achieve meaningful learnings to solve life’s problems, this originates in the new curricular perspectives contextualized to the current regulations and specific necessities of the environment where they occur and guide its operation, for this reason, the structure of educational models that orientate all the students’ necessities with links to the society; it will show that the school is involved to the current reforms, in which the student is considered as the center of all process through approaches and actions taken in the school as to the methodology to be applied; being the direct beneficiaries the educational community of Mariscal Antonio José de Sucre school.